SISTEM LAMPU PARKIRAN OTOMATIS BERBASIS ARDUINO UNO DAN SENSOR LDR PADA PARKIRAN GEREJA - Andreas Rofrans Sadewa Sitanggang; Hafni; Muhammad Zen (CV. Hawari, 2026)
Efficient use of electrical energy is a crucial aspect in the management of public facilities, including houses of worship. In church parking areas, manual lighting systems often lead to electricity waste. This research aims to implement lighting automation technology by utilizing an Arduino Uno microcontroller and a Light Dependent Resistor (LDR) sensor. Through a prototype design approach, this system was developed to detect the level of light intensity in the surrounding environment in real-time. Test results show the effectiveness of the system in controlling the lights: the device will activate the lights when the light intensity is above 850 lux (dim/dark conditions) and deactivate them when below 849 lux (bright conditions). The implementation of this innovation is expected to reduce electricity operational costs while increasing safety factors in the church environment.